Analisis Akad Kerjasama Bank Syariah Indonesia dengan Pondok Pesantren Darurrahmah Bogor Jawa Barat dan Kesesuaiannya dengan Fatwa DSN-MUI - Hidayat; Moehammad Abdul ‘Aziz; Taufiq Ramadhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The contain research in this analysis is about the contract used by Darurrahmah Islamic Boarding School and Bank Syariah Indonesia. This research is literature and field research by emphasizing the quality of data obtained from the literature focused on examining the role of Bank Syariah Indonesia in Darurrahmah Boarding School Bogor, West Java. The approach used by the researcher was descriptive qualitative by providing solutions to problems by collecting data, compiling, classifying, analyzing, evaluating, and interpreting them. The sources of data used in this study were in the form of primary sources, namely Bank Syariah Indoensia and the Boarding School Administration Division, as well as books related to this. In addition, there were also some secondary sources i.e. a journal entitled “Prospek dan Kendala Bank Syariah di Era Globalisasi” by Siti Yunitarini. The results show that the contract used by Darurrahmah Islamic Boarding School and Bank Syariah Mandiri branch of Cibubur related to monthly salaries and tuition fees for students are mudharabah muthlaqah and wadi'ah yad dhamanah contracts with the provisions described in this thesis. The author also concludes that there is an agreement between the contracts and the DSN-MUI fatwa related to these contracts in terms of the form for creating new savings accounts with the DSN-MUI fatwa accompanied by the results of interviews with several staff at the central and branch of Bank Syariah Mandiri